Effect of urea and malathion on the freshwater prawn, Macrobrachium lamarrei (H.M. Edwards) - Ali, Anjuman Ara; Mannan, MA; Parween, Selina (University Journal of Zoology, Rajshahi University, 2008)
Key words: Agro-chemical, berried, survivability, hatchability.Univ. j. zool. Rajshahi Univ. Vol. 26, 2007. pp. 107-108